BUSINESS ORGANIZATION - SHRAMA R K; SHASHI K GUPTA; PUNEET KUMAR (NOIDA KALYANI PUBLISHERS, 2024)
R.K. Sharma's "Business Organization" is a foundational textbook, primarily aimed at undergraduate students of commerce and business administration. Often co-authored with Shashi K. Gupta, the book provides a comprehensive introduction to the principles and practices of business organization and management. It is widely used in Indian universities and is known for its clear, concise, and systematic presentation of core concepts.
MANAGEMENT
Keywords: BUSINESS; MANAGEMENT